Improving patient care by effective streamlining of general paediatric discharges. (29th September 2015) - Sohi, D; Milne, C; Westland, O; Charles, T; Watson, M
Abstract : Introduction: There has been a recent shift in government policy towards ensuring that healthcare services for children are more child and family-centred. Ideally, any admission should be as short as possible, with aftercare supported by the "hospital at home" model. The authors studied the process of discharge in our unit to identify possible areas of avoidable delay and measures that may overcome them. Method: The time and action course leading to a patient's discharge was process-mapped. Five domains were identified: ▸ discharge medication ▸ completion of electronic discharge summary ▸ patient reviews ▸ patient transfers ▸ bed being cleaned and prepared for the next patient. Data were collected 24 h per day, over 8 days, from the time decision was made to discharge (TDD). Results: Data on 34 discharges were collected to completion. The average time from TDD to the patient leaving the ward was 4.5 h, and 6.6 h for the patient's bed to become available for the next patient. Discharge medication took 3.3 h to organise. The family took 6 h to organise transport with 70% of patients waiting for this by their bedside. Only 53% of patient discharges were discussed and organised prior to the ward round, leading to trainees often leaving the ward round to coordinate discharges. Discussion: This study has demonstrated multiple areas for improvement. We recommend that discharge should be discussed at admission. This will enable timely generation of discharge summaries and the families given an idea of potential discharge time so that they can make appropriate preparation. Dedicated discharge coordinators/nurses should join the ward round to ensure that the process runs seamlessly, and reduce the need for trainees to leave the ward round. Children requiring review should have a clear plan for discharge, which could be nurse-led. Every paediatric unit should identify waiting areas for children who have been cleared for discharge to ensure more efficient bed utilisation. Conclusion: With these measures in place, the new process-map of patient discharge generated 156 h of increased bed availability. This equates to almost an extra bed/cubicle per day, and could significantly reduce waiting times in A&E.